Oncologic Thermoradiotherapy: Need for Evidence, Harmonisation, and Innovation - Bodis, Stephan; Ghadjar, Pirus; Van Rhoon, Gerard C. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The road of acceptance of oncologic thermotherapy/hyperthermia as a synergistic modality in combination with standard oncologic therapies is still bumpy. This is partially due to the lack of level I evidence from international, multicentric, randomized clinical trials including large patient numbers and a long term follow-up. Therefore we need more level I EVIDENCE from clinical trials, we need HARMONISATION and global acceptance for existing technologies and a common language understood by all stakeholders and we need INNOVATION in the fields of biology, clinics and technology to move thermotherapy/hyperthermia forward. This is the main focus of this reprint. In this reprintyou find carefully selected and peer-reviewed contributions from Africa, America, Asia, and Europe. The published papers from leading scientists from all over the world covering a broad range of timely research topics might also help to strengthen thermotherapy on a global level.